2000
DOI: 10.1046/j.1365-2346.2000.00627.x
|View full text |Cite
|
Sign up to set email alerts
|

Postoperative nausea and vomiting after breast surgery: efficacy of prophylactic ondansetron and droperidol in a randomized placebo-controlled study

Abstract: Postoperative nausea and vomiting (PONV) is a common adverse phenomenon following breast surgery. The efficacy of ondansetron and droperidol in preventing post-operative nausea and vomiting in women undergoing breast surgery was compared in this randomized, double-blind, placebo-controlled study. Altogether 207 women were randomly assigned to receive either a single intravenous dose of droperidol (1.25 mg) (n = 69), ondansetron (8 mg) (n = 67) or saline (n = 71) immediately after induction of general anaesthes… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
10
1
1

Year Published

2004
2004
2020
2020

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 38 publications
(13 citation statements)
references
References 32 publications
1
10
1
1
Order By: Relevance
“…There was a low incidence of PONV during the first 24 h after surgery in the present study, different from results of previous studies regarding PONV associated with breast and thyroid surgery [1,2]. The incidence of PONV is known to be influenced by patient characteristics, type of surgical procedure, anesthesia technique, and postoperative analgesics [3].…”
Section: Discussioncontrasting
confidence: 99%
See 1 more Smart Citation
“…There was a low incidence of PONV during the first 24 h after surgery in the present study, different from results of previous studies regarding PONV associated with breast and thyroid surgery [1,2]. The incidence of PONV is known to be influenced by patient characteristics, type of surgical procedure, anesthesia technique, and postoperative analgesics [3].…”
Section: Discussioncontrasting
confidence: 99%
“…It has been reported that the incidences of PONV are between 60 and 80% for mastectomy and thyroidectomy, respectively [1,2]. The first step for the prevention of PONV is to reduce risk factors, i.e., by the use of propofol-based anesthesia and decreased use of intraoperative N 2 O and postoperative opioids.…”
Section: Introductionmentioning
confidence: 99%
“…[ 14 ] IV pre-treatment with a single dose of ondansetron also does not substantially prevent this. [ 15 ] Bakri et al . reported that reduction in the incidence and severity of PONV due to use of dexmedetomidine was almost similar to dexamethasone with analgesic superiority.…”
Section: Discussionmentioning
confidence: 99%
“…The incidence of nausea and vomiting was lower in group PCAIB in our study, although there was no significant difference between the two groups. One reason could be that a preemptive antiemetic, ondansetron, was used [ 22 ]. In addition, the regimen of PCA was constituted of fentanyl and ketorolac, which might cause less nausea and vomiting [ 23 , 24 ].…”
Section: Discussionmentioning
confidence: 99%